Audit of IT Governance Based on COBIT 5 Assessments: A Case Study - Johanes Fernandes Andry (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2016)
Training Center in Jakarta offers a certification program for the individuals and companies who wish to search for or complement international scale IT certifications. The certification program consists of training certification exam preparation and certification exams. The purpose of this research is to get an overview of the performance of information technology governance in order to determine the extent of the capabilities of information technology governance in the Training Center which is currently running, with a few aspects to consider such as effectiveness, efficiency, functional unit of information technology within an organization. Implementing IT governance, however, is a challenge to organizations. To ensure IT alignment with business goals use standard COBIT. COBIT 5 Framework is a service for auditing IS/IT are the most commonly used to audit information systems in a rapid, accurate, and interactive. The result of this audit training center is business and IT management are aware of the impact of not managing performance and capacity. Performance needs are generally met based on assessments of individual systems and the knowledge of support and project teams. In this paper the method to be used is COBIT 5 is focused on the domain of DSS (Deliver, Service, and Support).